A redescription of the type species of the jumping spider genus Pseudomaevia (Araneae: Salticidae) from Lord Howe Island, Australia - Richardson, Barry J. (Zootaxa, 2014)
The genus Pseudomaevia Rainbow, 1920 presently includes three forms, P. cognata Rainbow, 1920, P. insulana Berland, 1942 and P. i. aorai Berland, 1942, all found in the western Pacific region (Platnick 2014). The type species, P. cognata, was only briefly described with some poor illustrations of the male, but no information was given on the female. This situation makes placing species in this genus, or the genus in a wider context, difficult. The present work describes and illustrates both sexes of the type species. The female genitalia are unusual in that the insemination duct joins the fertilization duct without any apparent spermatheca. The subfamilial placement of the genus is unknown.